Ametropías y su relación con la calidad visual en los estudiantes de educación básica superior de la Escuela “Bahía de Caráquez” del Recinto Estero de Lagarto-cantón Vinces. Junio-septiembre 2024. - Jara Coello, Jesús Rafael (2024)
The present study focused on evaluating the relationship between ametropias (refractive defects such as myopia, hyperopia and astigmatism) and visual quality in Higher Basic Education students from the "Bahía de Caráquez" School. Conducted between June and September 2024, the main objective was to determine how these ocular defects affect the daily life of students and whether there is a direct relationship between ametropias and a decrease in visual quality. To this end, 77 students were evaluated, selecting a sample of 45 with ametropias diagnosed through optometric examinations. Visual acuity tests and a questionnaire were used to assess vision-related quality of life. The results revealed a high prevalence of ametropias in the sample, with astigmatism being the most common. Likewise, a correlation was observed between the presence of ametropias and a decrease in the visual quality of life reported by the students. These findings highlight the importance of conducting periodic visual assessments in the student population and of providing attention to refractive problems in order to improve their quality of life and academic performance. This study highlights the need to address the problem of ametropias in the school population, since these significantly affect visual quality and can impact the academic and personal development of students. The results obtained contribute to raising awareness about the importance of visual health and the need to implement early detection and treatment programs for refractive defects in educational environments.